Sexual Dimorphism in Human Mandibular Canine Teeth: A Radiomorphometric Study - K S Nagesh; Asha R lyengar; Rishabh Kapila; Sushma Mehkri (Wolters Kluwer Medknow Publications, 2011)
Objectives: The objective of this study was to determine whether the variation in the mesiodistal measurement of mandibular canine played a role in sex determination. Materials and methods: The study comprised of patients in the age group of 19 to 24 years (20 males and 20 females). Mesiodistal measurement of mandibular canines was measured at the maximum mesiodistal width first intraorally, then on plaster models of the same patient followed by intraoral periapical radiograph of the same patient. Results: From the findings of the study, it may be inferred that there exists a definite statistically significant difference in the mesiodistal width of mandibular canines when measured for males and females. Moreover, the left mandibular canine showed a greater sexual dimorphism (9.7%) when compared to the right mandibular canine (7.4%) Conclusion: The present study establishes a statistically significant sexual dimorphism in mandibular canines- It can be concluded that the standard mandibular canine index is a quick and easy method for sex determination.